Lawyer's ready referencer ( Civil) - Rao, Y. Rama. (Hyderabad, 2003)
This thoroughly revised and enlarged edition contains some new features added to make it more useful to the readers. New Chapters and new Topics have been created for easy reference. The names of the parties in each case have been added. Table of Cases is included and the Subject Index is also given at the end of the Book. Further, new case-law has been added while deleting the case law which has become either overruled or corrected in a subsequent decision when the earlier ruling was rendered per incurium. This book is brought up to the end of the year 2002.
Keywords: "Lawyers-Handbooks, manuals, etc."